(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Composite films of both Poly (vinyl alcohol)/nano silica-nano zinc oxide (PVA/SiO2- ZnO) and Poly (methyl methacrylate) / nano silica-nano zinc oxide -chlorophyll (PMMA/SiO2-ZnO-Ch) are prepared by using casting method and their medical applications are evaluated. In this study Nano, silica and Nano zinc oxide are used as filler with the following percentages of (1, 2 and 3) to improve the biological and mechanical properties of the composite films. Many tests are carried on the composite films such as Fourier transform infrared spectroscopy (FTIR), antibacterial activity, and tensile test. Their results show that zinc oxide has an excellent antibacterial activity and this activity increases in composite films with the increasing concentration of the zinc oxide .PMMA composite films show a better healing power than that of the PVA composite films. To avoid cracking on the produced PMMA film, chlorophyll as a bio natural pigment, is added it acts as a plasticizer and as a result it removes film stresses. All mechanical and physical tests show that the PVA composite has higher values than those of PMMA. This is due to the fact that PVA can build a hydrogen bond with ZnO or SiO2 additives while PMMA has no tendency for H-bonding.